2009
DOI: 10.1099/vir.0.008722-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for modulation of BAG3 by polyomavirus JC early protein

Abstract: Polyomavirus JC (JCV) infects oligodendrocytes and astrocytes in the brain and is the cause of the demyelinating disease progressive multifocal leukoencephalopathy (PML). In cell culture, JCV infection is characterized by severe damage to cellular DNA, which begins early in infection, and a viral cytopathic effect, which is observed late in infection. Nevertheless, these JCV-infected cells show a low level of apoptosis, at both the early and late stages of infection. This suggests that there is conflicting int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Affected viruses include varicella-zoster virus (VZV), 68 polyomavirus JC, 69 Epstein-Barr virus (EBV), 70 herpes simplex virus (HSV) 71 and HIV 72 . In many cases, depletion of BAG3 by small interfering RNA inhibits virus replication.…”
Section: A Unifying View On the Multifaceted Cochaperone Bag3mentioning
confidence: 99%
“…Affected viruses include varicella-zoster virus (VZV), 68 polyomavirus JC, 69 Epstein-Barr virus (EBV), 70 herpes simplex virus (HSV) 71 and HIV 72 . In many cases, depletion of BAG3 by small interfering RNA inhibits virus replication.…”
Section: A Unifying View On the Multifaceted Cochaperone Bag3mentioning
confidence: 99%
“…Furthermore, T-Ag induces cell growth by interacting with cellular transcription pre-initiation complexes, binding to cellular DNA, DNA polymerase α, and ATPase-helicase [12], [13]. In a previous study we demonstrated that JCV T-Ag inhibits expression of Bag3, a member of the Bag, Bcl-2-associated athanogene) family of molecular co-chaperone proteins [14], during the course of productive viral infection of glial cells by suppressing transcription of the Bag3 promoter [15]. Bag3 was initially discovered based on its binding ability to Bcl-2 [16] and has been implicated as a modulator of cellular responses to stress by interacting with the ATPase domain of Hsc70/Hsp70, and suppressing the chaperone activity of the complex [17].…”
Section: Introductionmentioning
confidence: 97%
“…The prosurvival activity of Bis was supported by later studies showing that Bis is overexpressed in several types of cancer and that the downmodulation of Bis sensitizes the apoptosis of tumor cells induced by chemotherapeutic agents and proteasome inhibitors (9,32,38,39). In addition to the prosurvival activity of Bis, its induction under a variety of stresses in vitro as well as in vivo, including hypoxia and viral infections (3,4,25,31,33,40), suggests that Bis might function as an antistress protein to modulate cellular response, thereby protecting cells from unfavorable environmental stresses. Other biological functions in which Bis is involved include the promotion of differentiation as shown in promyelocytes or E19 embryonic stem cells (45), the regulation of motility migration and invasion (20,24,26), and protein quality control via the promotion of autophagy (5,13,16,19).…”
Section: Mice the Bismentioning
confidence: 97%